New local anesthetics. Issue 2 (June 2018) - Shah, Jarna; Votta-Velis, Effrossyni Gina; Borgeat, Alain
Abstract : Local anesthetics are used for performing various regional anesthesia techniques to provide intraoperative anesthesia and analgesia, as well as for the treatment of acute and chronic pain. Older medications such as lidocaine and bupivacaine as well as newer ones such as mepivacaine and ropivacaine are being used successfully for decades. Routes of administration include neuraxial, perineural, intravenous, various infiltrative approaches, topical, and transdermal. There are new innovations with the use of older local anesthetics in a novel manner, in addition to the development and use of new formulations. This chapter seeks to summarize the pharmacokinetics of local anesthetics and address the role of newer local anesthetics, as well as clinical implications, safety profiles, and the future of local anesthetic research. Finally, some clinical pearls are highlighted. Highlights: Local anesthetics are currently known to be not only sodium channel blockers but also blockers of many different receptors. New short-acting local anesthetics have a promising potential in the context of day case surgery. The benefit of the new liposomal bupivacaine formulation is still unclear. The application of IV lidocaine in the context of any inflammatory process including cancer metastases is of great interest.